English and Vietnamese business complaint letters - a comparative study from systemic functional perspectives - Lại, Thị Thanh (ĐHNN, 2017)
his study is comprised of three parts: Part One of this study is an introd uction presenting some background information and the rationale of the study. T he aims, the scope and method of the study are also dealt with in this chapter. Part T wo consist of three chapters. Chapter O ne is aimed to present the theoretical background of the work. Some essential concepts closely related to the study are carefully discussed one by one . Firstly , some theories of disc ourse including the concept of discourse, functions of language, and discourse context. Next, in terms of Systemic Functional Grammar, some concepts such as transitivity, mood, theme - rheme, and cohesion consisting of reference , s ubstitution , e llipsis , l ex ical cohesion , and conjunctive c ohesion are presented. Finally, the definition, purpose, three contextual parameters and structure of business complaint letters are also discussed in the chapter. Chapter T wo attempts to analyze business complaint letters i n both English and Vietnamese in the light of Systemic Functional Grammar . In this chapter, the four chosen terms of transitiv ity, mood, theme - rheme and cohesion which consists of reference, substitution, ellipsis , lexical cohesion and conjunctive cohesion are carefully analyzed to help figure out the differences and similarities of business complaint letters in the two languages in the next chapter. Chapter Three is concerned with the discussion of the similarities and differences between English and Viet namese business complaint letters in terms of transitivity, mood, theme - rheme and cohesion. The last part is set up to summarize the whole research. Some useful implications for studying and teaching writing effective business complaint letters are also d rawn out in this chapter